2016
DOI: 10.1111/jpm.12327
|View full text |Cite
|
Sign up to set email alerts
|

Development and preliminary evaluation of culturally specific web‐based intervention for parents of adolescents

Abstract: Accessible summary What is known on the subject? Problematic parent–child relationships have been identified as one of the main predictors of adolescents' mental health problems, but there are few existing interventions that address this issue. The format and delivery method of existing interventions for parents are relatively inaccessible for parents with full‐time jobs and families living in rural areas. What does this paper add to existing knowledge? The newly developed ‘Stepping Stone’ culturally spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(46 citation statements)
references
References 55 publications
(50 reference statements)
2
44
0
Order By: Relevance
“…The total score ranges from 20 to 40, with a higher score indicating a high level of parent-child conflicts. This scalehad acceptable reliability in the previous studies (α=.89∼.92) (Choi et al, 2012;Choi et al, 2016), and in this study (α=.88).…”
Section: ) Quantitative Datasupporting
confidence: 72%
See 1 more Smart Citation
“…The total score ranges from 20 to 40, with a higher score indicating a high level of parent-child conflicts. This scalehad acceptable reliability in the previous studies (α=.89∼.92) (Choi et al, 2012;Choi et al, 2016), and in this study (α=.88).…”
Section: ) Quantitative Datasupporting
confidence: 72%
“…The sample for the present study was drawn from a larger study which was designed to test the efficacy of a newly developed 4-week online parent education program for Korean parents of adolescents, "Stepping Stone." Descriptions of the larger study are discussed elsewhere (Choi et al, 2016). The…”
Section: A Brief Description Of the Larger Study And Study Proceduresmentioning
confidence: 99%
“…The final articles included in this systematic review consisted of multiple designs. There were 2 randomized controlled trials [ 33 , 80 ], 1 quasi-experimental study [ 81 ], and 2 qualitative studies [ 82 , 83 ]. In all 5 articles, the caregivers had been exposed to communication technologies in caring for adolescents with mental health issues.…”
Section: Resultsmentioning
confidence: 99%
“…First, the most frequently reported challenge in technology-based interventions is that participants must be able to use the technology involved in the intervention, and because of this, participants are more likely to be a select group of people. [9][10][11][12] For instance, participants tended to be highly educated Caucasians, even when they were recruited from rural areas or as older adults. In this study, all participants needed the ability to use a computer and/or smart phone technology, which surely limited the sample population similar to previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Thus, the validity and reliability of the data depend mainly on participants' desire to use and accept the technology. 31 In addition, low retention rates for technology-based interventions were frequently reported, [9][10][11][12] I because the participants simply did not finish the intervention, 32 could easily drop out of the study without consequences, 33 and/or did not feel comfortable about using technology (although they were willing to use). 34 In this study, the same issues related to low recruitment and retention rates were identified among Asian American survivors of breast cancer.…”
Section: Discussionmentioning
confidence: 99%